7x+3y=-2

Simple and best practice solution for 7x+3y=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3y=-2 equation:


Simplifying
7x + 3y = -2

Solving
7x + 3y = -2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
7x + 3y + -3y = -2 + -3y

Combine like terms: 3y + -3y = 0
7x + 0 = -2 + -3y
7x = -2 + -3y

Divide each side by '7'.
x = -0.2857142857 + -0.4285714286y

Simplifying
x = -0.2857142857 + -0.4285714286y

See similar equations:

| (7x+4y)dx+(4x+8y^3)dy=0 | | 4=3a+1 | | 2.094x=20 | | x-(-7)+8=13 | | 10x-5y+15=0 | | 63/7= | | a=3a+1 | | 20.6=g-85.43 | | -2(x-4)=x+7 | | 7(-b+2)=9(-2b-17) | | 2(9-x)=6(x-8) | | 7n+(-1)/8=8 | | 3x-1-(1+2x)=1 | | 3.5w-35=w | | Sm=m(11+3m) | | -6m-10=88 | | 0.25(8w-4)=w+8-2w | | 3.5w-25=w | | 3.5w-25=w | | 2.094x=12 | | 6a+8x-8a+6ax-x= | | 6x+5(x-3)=-7 | | 11x+2=2(4x+1)-x+9 | | 50g=3g+(-552)+1g | | 54=(x*39.04) | | -4x+3(3x-5)=31 | | -4k+55=8k-29 | | -x+3+15x=-6+5x+54 | | (5ab)+(-9ab)= | | 136-7x=38x+16 | | -5-(3m+6)=-3(4m-2) | | 2.094x=4 |

Equations solver categories